2017
DOI: 10.1177/2333794x17745973
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Accelerometer Versus Self-Report Sleep Assessment in Youth With Concussion

Abstract: This study examines accelerometer-based and self-report assessment of sleep disturbance from a larger prospective cohort of youth 5 to 18 years of age with postconcussive injury. Twenty-one participants with self-reported sleep disturbance were evaluated using accelerometers. Participants completed the Pittsburgh Sleep Quality Index (PSQI) every 48 hours and also measured sleep via accelerometry. Correlations were conducted matching PSQI scores to accelerometry assessment. PSQI scores were significantly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 97 publications
1
12
1
Order By: Relevance
“…Surprisingly, different results were observed when the association between sleep quality and energy metabolism was performed considering subjective instead of objective measures of sleep quality. It has been previously reported that PSQI and accelerometer records measure different attributes of sleep, highlighting the bias of accelerometry to register wakefulness, thus lying in bed awake but motionless is likely to be coded as sleep 63 . Therefore, it is recommended to use both methods to obtain complementary information additionally to the body movements 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, different results were observed when the association between sleep quality and energy metabolism was performed considering subjective instead of objective measures of sleep quality. It has been previously reported that PSQI and accelerometer records measure different attributes of sleep, highlighting the bias of accelerometry to register wakefulness, thus lying in bed awake but motionless is likely to be coded as sleep 63 . Therefore, it is recommended to use both methods to obtain complementary information additionally to the body movements 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed different results when the association between sleep quality and body composition was performed considering subjective sleep quality measured by a PSQI questionnaire versus objective sleep quality measured with an accelerometer. A previous study in youth observed that the PSQI and the accelerometer may measure different attributes of sleep, reporting the inadequate capacity of an accelerometry to detect wakefulness, thus lying in bed awake but motionless is likely to be coded as sleep [ 51 ]. Due to this limitation, using both complementary assessment methods (objective and subjective) to obtain detailed information beyond the limited data derived from body movements, is recommended [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research should explore the use of objective measures in addition to subjective measures when studying physical activity 7 and sleep. 57 Future research should explore other pre-and post-injury factors that can influence activities and participation in adolescents and young adults after mTBI such as deconditioning, increasing demands on participation, or psychosocial issues.…”
Section: 1mentioning
confidence: 99%